Isolated fracture of the lesser tuberosity of the humerus – a rare injury that requires surgical treatment - Glišić, Miodrag; Stevanović, Vladan; Jevtić, Aleksandar; Jovićević, Uroš; Janković, Ivan (Vojnosanitetski pregled, 2023)
Introduction. An isolated fracture of the small tuberosity is a very rare injury that can often be overlooked. That injury is significant due to the function of the subscapularis muscle, which loses its attachment by separating the small tuberosity. Case report. A 45-year-old male, former athlete, suffered a left shoulder injury while falling downhill. Although the clinical picture was not convincing, a computed tomography scan showed a fracture. Open repositioning and osteosynthesis were performed. After rehabilitation, the patient regained a full active range of motion in the shoulder joint three months after the operation. We present the mechanism of injury, clinical picture, necessary diagnostics, and technique of surgical treatment of isolated fracture lesser tuberosity of the humerus. The results of other authors whose series are also quite small were analyzed. Conclusion. It was concluded that an isolated fracture of the small tuberosity requires surgical treatment to preserve a good range of motion in the shoulder joint.
Keywords: diagnosis; fractures, avulsion; humeral fractures; orthopedic procedures; tomography, x-ray, computed